A retrospective public health analysis of the Republic of Ireland's Food Harvest 2020 strategy: absence, avoidance and business as usual. Issue 1 (1st January 2018) - Kenny, Tara; Cronin, Mary; Sage, Colin
Abstract: The concept of an Ecological Approach to health and including Health in All Policies warrants inter-sectoral and transdisciplinary collaboration to improve health determinants and reduce health inequities. Agriculture policies, which greatly influence food production and its environmental impacts as well as food availability and dietary consumption, are therefore of interest to public health. Increasing rates of non-communicable diseases linked to diets containing high levels of processed foods, increasing numbers of households unable to access nutritious food and the environmental consequences of the food system are amongst the major health challenges of today, both globally and in Ireland. In 2010, Ireland's Department of Agriculture, Food and Fisheries published Food Harvest 2020 a roadmap for Irish agriculture for the subsequent decade prepared against a backdrop of rising diet-related ill-health and increasing environmental concerns. This article critically analyses the process of consultation and stakeholder involvement in the development of Food Harvest 2020 from a public health perspective. Publically available documents including submissions to the Food Harvest 2020 consultation process were the primary source of data. This study highlights a distinct absence of public health representation in the process, an avoidance of some key public health challenges and the dominance of a 'business as usual' approach.